Preparasi Matriks Alam Sekresi Kutu Lak Dengan Asam Adipat Pada Biokomposit Serat Rami - Prianto, Hestya Arinta Ayu; Ruspita, Roza; Rohaeti, Eli (Hydrogen: Jurnal Kependidikan Kimia, 2020)
In this research, preparation of natural matrix from modified flea secretion (SKL) by the addition of adipic acid as matrix in biocomposites of ramie fiber have been carried out. This research was initiated by dissolving the chunks of flea secretion using ethanol with ratio 1:2 and heated at temperature 50oC. Flea secretion has modified by the addition of adipic acid in various concentration 5%, 10%, 15%, 20%, and 25%. Viscometry technique with viscometer ostwald was used for characterizing intrinsic viscosityof natural matrix. The optimum value of intrinsic viscosity were reached at concentration 5% of adipic acid that has 77,08 mg/l viscosity. Biocomposites were made by mixing ramie fibers and natural matrix SKL which have been modified by the addition of adipic acid with optimum concentration at 60:40ratio of fibers: matrix. Biocomposites were evaluated for mechanical properties with ASTM D638 type IV standard. Biocomposite sampel was formed specimens and tested with tensile tester. Biocomposite from ramie fibers and natural matrix SKL modified by adipic acid has a tensile strength 15,14 MPa and elastic modulus was 1519,15 MPa.